Ska det vær nu? Verbale kortformer i regulerede og ikke-regulerede genrer - Rathje, Marianne (Danske Studier, 2024)
In the 1970s, Allan Karker (1976) noticed that verbal short forms like gir, ku, sku and ha were more frequently used in Danish than their long forms, and he therefore suggested to The Danish Language Council that these abbreviated forms should be allowed in the official dictionary of Danish standard orthography – a suggestion that was not accepted. In new media, such as text messages and Facebook, the verbal abbreviations are used once more as a general reduction (White 2014, 2015) in the language of these genres. This article investigates whether these verbal short forms are more frequently used in certain genres, and whether there is a renewed basis for considering whether or not the verbal abbreviations should be allowed in the official dictionary. The data of this study are composed of texts from various Danish newspapers (1990–2014), the text corpus KorpusDK, comments from the online tabloid newspaper ekstrabladet.dk, text messages and Facebook messages written by young people, school essays, and interviews with the same young people – the latter to illustrate present attitudes to and functions of the short forms as well.